Pengaruh Advertising Dan Kualitas Pelayanan Terhadap Proses Keputusan Pemilihan Universitas (Studi Kasus di Universitas Muhammadiyah Tangerang) - Susanti, Yanti Susan; Hamdani, Hamdani; Lobis, Enyk Usmany (Universitas Muhammadiyah Tangerang, 2024)
This research aims to determine the influence of advertising and service quality on the decision process of students choosing Muhammadiyah University, Tangerang. The research approach used in this research is quantitative research. Statistical tests were carried out which included simple regression tests, multiple regression tests, simple correlation tests, multiple correlation tests, and determination of determinant coefficients. And hypothesis testing is also carried out, including partial tests (t tests) and simultaneous tests (F tests). Data processing analysis used the SPSS version 23 program. The sampling technique used in this research was Sample Random Sampling, obtaining a sample of 133 respondents. The data collection technique uses a questionnaire given to students in the 2014 to 2017 academic year at Muhammadiyah University, Tangerang. The partial calculation results obtained for advertising tcount are greater than ttable, namely 6.275>1.652. And for service quality tcount is greater than ttable is 7.099>1.652. This means that partially there is a positive and significant contribution between advertising and service quality to the student decision process. Simultaneous testing obtained that Fcount was greater than Ftable, namely 34.721>3.04. This means that simultaneously there is a positive and significant contribution between advertising and service quality to the student decision process